Molecular cloning of nif DNA from Azotobacter vinelandii. - Bishop, P E (1985)
Two clones which contained nif DNA were isolated from a clone bank of total EcoRI-digested Azotobacter vinelandii DNA. The clones carrying the recombinant plasmids were identified by use of the 32P-labeled 6.2-kilobase (kb) nif insert from pSA30 (which contains the Klebsiella pneumoniae nifK, nifD, and nifH genes) as a hybridization probe. Hybridization analysis with fragments derived from the nif insert of pSA30 showed that the 2.6-kb insert from one of the plasmids (pLB1) contains nifK whereas the 1.4-kb insert from the other plasmid (pLB3) contains nifD. Marker rescue tests using genetic transformation indicated that the 2.6-kb A. vinelandii nif fragment contains the wild-type alleles for the nif-6 and nif-38 mutations carried by Nif- strains UW6 and UW38. The 1.4-kb insert contains the wild-type allele for the nif-10 mutation carried by Nif- strain UW10.